Censorship of Literature in Austria 1751-1848 - Bachleitner, Norbert (Verlag der Österreichischen Akademie der Wissenschaften, 2022)
The influence of censorship on the intellectual and political life in the Habsburg Monarchy during the period under scrutiny can hardly be overstated. This study examines the institutional foundations, operating principles, and results of the censorial activity through analysis of the prohibition lists and examination of the censors themselves. Ten case studies focus on individual works forbidden by the censors, an annex documents the most important regulations along with a selection of censorial reports. German version: https://e-book.fwf.ac.at/o:1102